The Dirty South contemporary art, material culture, and the sonic impulse - Bradley, Regina N.; Braxton, Charlie R.; Brownlee, Andrea Barnwell 19XX-; Buick, Kirsten Pai; Burris, Jennifer; Combs, Rhea L.; McArthur, Park 1984-; DJ Spooky That Subliminal Kid 1970-; Moten, Fred 1962-; Pinn, Anthony B.; Ramsey, Guthrie P.; Reeves, Roger (Virginia Museum of Fine Arts, 2021)
Director's foreword / Alex Nyerges -- What you know about the Dirty South? / Valerie Cassel Oliver -- a poem for black art / Fred Moten -- Landscape : the politics and poetics of dirt. Cosmic encounter / Charlie R. Braxton ; Bevery Buchanan : forms of ruination / Andrea Barnwell Brownlee, Jennifer Burris, and Park MacArthur ; Quilted beats bound at the rut : a theorization of the Dirty South / Regina N. Bradley ; Plates -- Systems of thought : the vision of envisioning. Songs that are sacred and pure (for Toni Morrison) / Charlie R. Braxton ; Dreaming empire, conjuring freedom : Renée Stout, African American landscape representation, and the imperial South / Kirsten Pai Buick ; Bible Belt swag : Houston hip-hop and Black religion / Anthony B. Pinn ; Dreaming of the South in stereo : Black music's American journey / Guthrie P. Ramsey Jr. ; Plates -- The Black body : repository/site/agent. Bluesosophy (for Julius Thompson) / Charlie R. Braxton ; Picturing the South : how photographers have imaged the region / Rhea L. Combs ; Changing the rules, the practice of pleasure : the linguistic possibilities of dirt / Roger Reeves ; Plates -- Epilogue. Code Black : the Dirty South / Paul D. Miller ; The Dirty South playlist ; Plates -- Artist biographies -- Contributor biographies -- Exhibition checklist and image credits
"This catalogue accompanies the exhibition The Dirty South: Contemporary Art, Material Culture, and the Sonic Impulse, presented at the Virginia Museum of Fine Arts, May 22-September 6, 2021; Contemporary Arts Museum Houston, October 28, 2021-February 6, 2022; Crystal Bridges Museum of American Art, March 12-July 25, 2022; Museum of Contemporary Art Denver, September 2022-February 2023"--Page iv
Includes artists: Terry Adkins, Charles Henry Alston, Emma Amos, Benny Andrews, Radcliffe Bailey, Romare Bearden, Kevin Beasley, Paul Stephen Benjamin, Julia Beverly, John Biggers, Sanford Biggers, Herman Poole Blount (AKA Sony'r Ra or Sun Ra), Sheila Pree Bright, Beverly Buchanan, Bisa Butler, Elizabeth Catlett, Nick Cave, Mel Chin, Sonya Clark, Bethany Collins, Eldzier Cortor, Abraham Lincoln Criss, Jamal Cyrus, Bruce Davenport Jr. (AKA Dapper Bruce Lafitte), Beauford Delaney, Thornton Dial, Nathaniel Donnett, Aaron Douglas, William Edmondson, Melvin Edwards, Winton and Rosa Eugene, Minnie Evans, Leonard Freed, Theaster Gates, Sam Gilliam, Allison Janae Hamilton, David Hammons, Bessie Harvey, Palmer Hayden (AKA Peyton Cole Hedgeman), Robert Hodge, Earlie Hudnall, Jr., Clementine Hunter, Arthur Jafa, Anderson Johnson, William H. Johnson, Richard FIEND Jones (aka International Jones), Jacob Lawrence, El Franco Lee II, Samella Lewis, James Little, Whitfield Lovell, Jonathan Mannion, Kerry James Marshall, James Martin (AKA Spider Martin), Rodney McMillian, Michi Meko, Jason Moran, Sister Gertrude Morgan, Marilyn Nance (AKA Soulsista), Rashaad Newsome, Tameka Jenean Norris (AKA T.J. Dedeaux-Norris and Meka Jean), Demetrius Oliver, Joe Overstreet, Fahamu Pecou, Rita Mae Pettway, Robert Pruitt, Deborah Roberts, Nadine Robinson, Sulton Rogers, RaMell Ross, Nellie Mae Rowe, Kenneth Royster, Paul Rucker, Augusta Savage, Joyce J. Scott, John Sims, Kevin Sipp, Kaneem Smith, Renée Stout, Jimmy Lee Sudduth, Felandus Thames, Alma Thomas, James Thomas (AKA Son Ford), Bob Thompson, Mildred Thompson, Mose Tolliver, Bill Traylor, Freeman Vines, Kara Walker, Nari Ward, Arliss Watford, Jack Whitten, William T. Williams, Purvis Young
Keywords: Geschichte 1945-2021; Kunst; Schwarze; USA -- Südstaaten; African American art / Southern States / 20th century / Exhibitions; African American art / Southern States / 21st century / Exhibitions; Material culture / Southern States / Exhibitions; African Americans / Music; African Americans / Religion; African American art / Political aspects / Southern States; African American art; African Americans; African Americans; Religion; Material culture; Exhibition catalogs; Music; Southern States / In art / Exhibitions; Southern States; Ausstellungskatalog -- Virginia Museum of Fine Arts -- 22.05.2021-06.09.2021 -- Virginia; Ausstellungskatalog -- Contemporary Arts Museum Houston -- 28.10.2021-06.02.022 -- Houston; Ausstellungskatalog -- Crystal Bridges Museum of American Art -- 12.03.2022-25.07.2022 -- Bentonville; Ausstellungskatalog -- Museum of Contemporary Art Denver -- 01.09.2022-02.2023 -- Denver